Impact of COVID-19 pandemic on medical and non-medical students at a private university in Malaysia - Li Ming, Ang; Yee, Saw Sen; Elanggovan, Keerthana; Wei, Chery Pang Yi; Rai, Saraswathi Bina (International Journal Of Community Medicine And Public Health, 2024)
Background: Worldwide the COVID-19 pandemic affected people in various ways. Despite all the constraints students were in a unique position of being thrown into a lockdown situation where they had to learn from home and online. This had its own repercussions, and our aim was to study the effect of learning, as well as the mental and financial impact it had on the students at this private university. Methods: Using a pre-validated google questionnaire, we conducted a cross-sectional study amongst the undergraduate students from the various faculties. We used a modified DASS-21, with 15 questions rated on a Likert’s scale to assess mental health. Academic assessment and the financial impact assessment had 8 questions each. Sample size was 177. Cronbach’s for overall internal consistency was 0.860. Results: We had 208 respondents, where 66.3% were female and 62% Chinese. The mean score for medical students (mean=38.3, SD=12.9) was slightly higher than non-medical students (mean=37.3, SD=11.6). Overall non-medical students faced more challenges than the medical students academically as seen in poor contact with lecturers (chi square 10.73, p=0.030), their home environment was not conducive for learning (chi square 4.38, p=0.036) and have significantly more distraction from family members (chi square 4.87, p=0.027). Financially, a significant number of non-medical students struggled to pay for food expenses (chi square 12.92, p≤0.001). Conclusions: There was no significant difference between medical and non-medical students on mental health issues. Non-medical students were impacted more academically and financially.